Experimental research of scattering coefficient of triangle diffuser made with charcoal - Khrystoslavenko, Olga; Grubliauskas, Raimondas (International Conference “Environmental Engineering”, 2023)
The acoustic diffuser is the device that distributes the acoustic energy of intense reflections through their spatial and temporal dispersion. The device for reduction of unvented acoustic effects and improves indoor sound quality. Triangle diffusers are made of wood plates and covered with charcoal elements. The high sound reflection co-efficient of charcoal is in the production of diffusers. Charcoal is an ecologically friendly and natural material. The result of studies of the triangle diffusers made of charcoal showed high values of the sound scattering coefficient, with a maximum value (of 87) at the frequencies of 2000 with 80% of charcoal. Increasing the percent of charcoal increasing in sound scattering. The device installs in the audiences of concert halls, recording rooms, and museums.
Keywords: acoustic diffuser; reverberation chamber; reverberation time; sound diffusion; sound scattering coefficient; wood charcoal